What led Thai-Buddhist background-believers to become Christian? A grounded-theory study - Hilderbrand, Kelly Michael (Missiology, 2020)
The central question of this grounded-theory study was what do Thai-Buddhist background-believers perceive as factors or influences that led them to become Christian? Other studies have been done to identify factors or reasons Thai people become Christian. Still, few qualitative or mixed studies have been done on this subject. This study identified three factors that Thai-Buddhist background-believers expressed as influences or factors in their Christian conversion: feeling dissatisfaction, encountering cognitive dissonance between Buddhist and Christian worldviews, and supernatural encounters with God. The significant component in the majority of accounts was a supernatural encounter that influenced the convert’s decision to become a Christian. Furthermore, in every situation, the participant made a conscious decision to seek God or to find more information about God.